Case Study Of Flextronics Technology Sdn Bhd - Mok, Fock Lin (2005)
The case study is conducted with the objectives to access the practicality of lean production concept in electronics contract manufacturing environment, to develop a measuring system to measure the effectiveness of lean production system for electronics circuit board assembly and to develop a general guideline for lean production system implementation in electronics circuit board assembly plant.